Development of an electrocardiographic classification tool using frontal plane vectorcardiogram - Nagenthiran Thurairaj (2008)
This master thesis describes a study of vectorcardiograms and the development of a classification tool for abnormal electro-cardiological states. This study involves the reconstruction of the equivalent-dipole heart electrical-activity vector for the QRS complex from bipolar leads voltages of actual ECG recordings, whose locus could be used to facilitate the assessment of intra-myocardial depolarization activity. The path of the locus is termed as the frontal plane Heart-Depolarization Vector Cardiogram (HDVC), which is actually a loop, with initial and terminal points at the origin (equivalent to the isoelectric baseline).